1994
DOI: 10.1111/j.1151-2916.1994.tb09772.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Sr2Ce2Ti5O16 in the System SrO‐CeO2‐TiO2

Abstract: The ternary system SrO-CeO,-TiO, was investigated using X-ray diffractometry. The formation of a new compound, Sr,Ce,Ti,O,,, was established, and its compatibilities with SrO, SrCeO,, and SrTiO, were studied. The results revealed the existence of a series of compounds Sr,-,,Ce,Ti,O,, and solid solutions Sr,+,Ce,Ti,+,O,,+,, (n I 6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 1 publication
4
13
0
Order By: Relevance
“…However, the XRD results of the attempted reactions indicated that the solid solutions did not form, instead NpOj, Ti02, and a cubic phase were present. The latter is very likely a solid Solution within the series [16]. The inability to prepare Sr2An2Ti50,6 and their solid solutions with SraCejTijOje was consistent with similar behavior previously encountered in trying to prepare the Pu(IV) Compounds SrjPujTijOjft and Sr2Ce2-jPu^Ti50,6 [11].…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…However, the XRD results of the attempted reactions indicated that the solid solutions did not form, instead NpOj, Ti02, and a cubic phase were present. The latter is very likely a solid Solution within the series [16]. The inability to prepare Sr2An2Ti50,6 and their solid solutions with SraCejTijOje was consistent with similar behavior previously encountered in trying to prepare the Pu(IV) Compounds SrjPujTijOjft and Sr2Ce2-jPu^Ti50,6 [11].…”
Section: Resultssupporting
confidence: 73%
“…While no Np(III) analog of SrLn2Ti40i2 was obtained, it was expected that Np(IV) would be stable in Compounds similar to Srfi.is^.Ces^TijOis [16], Thus, attempts were made to prepare the An(IV) (An = Am or Np) analogs of Sr2Ce2Ti50,6, a member of the series Sr6-,2^Ce6^Ti50,6 where x ~ 0.33. This series of Compounds is perovskite-like with XRD pattems and lattice parameters very similar to the series Sr4_^Ln2,/3Ti40,2 where x < 2.84 (cubic slightly distorted to tetragonal) [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sr2Ce2Ti5O16 compound was reported by Bamberger et al [4] with pseudo cubic structure and its microwave dielectric properties i.e. r~113, high Qufo~8000 GHz and f~306 ppm/ o C were reported by Subodh et al [5].…”
Section: Introductionmentioning
confidence: 99%